ANALYZING THE BUDGET PERFORMANCE OF THE EAST KALIMANTAN PROVINCIAL HEALTH OFFICE FROM THE ACCOUNTABILITY AND TRANSPARENCY PERSPECTIVE - Lusia Ramanita; Jamaluddin Jamaluddin; Annisa Abubakar Lahjie (University of Widya Gama Mahakam Samarinda, 2026)
This study aims to examine the effect of accountability and transparency on budget performance at the Provincial Health Office of East Kalimantan. A quantitative survey approach was employed. The population comprised 412 civil servants (ASN) and government contract employees (PPPK) involved in budget planning, implementation, and reporting. Purposive sampling was applied based on the criterion of direct involvement in the budgeting process, yielding 50 respondents. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS 4.0). Results indicate that accountability has no significant effect on budget performance (t-statistic = 0.009; p-value = 0.993), whereas transparency has a significant and positive effect (t-statistic = 4.485; p-value = 0.000). These findings suggest that transparency is a key determinant of budget performance in the public sector, while accountability in this context remains oriented toward procedural compliance rather than performance improvement.